Convergence of inertial hybrid splitting algorithms - Semenov, V.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
Two new algorithms for solving the operator inclusion problems with maximal monotone operators acting in a Hilbert space are proposed. Algorithms are based on the inertial extrapolation and three well-known methods: Tseng forward-backward splitting algorithm and two hybrid algorithms for the approximation of fixed points of nonexpansive operators. Theorems on the strong convergence of the sequences generated by the algorithms are proved.